The conversion of cognitive interjections in classical English literature into Indonesian - Nadia Khumairo Ma'shumah; Arif Nur Syamsi; Susana Widyastuti (LITERA, 2023)
Translating interjections is notoriously challenging. Aside from their ambiguous and context-dependent meanings, they also express emotions through broadly suggestive sensations, attitudes, and states of mind. This study attempts to uncover emotional meanings embedded in cognitive interjections, the conversion strategies of cognitive interjections, and how the conversion strategies affect correspondence and equivalence. The data were interjective expressions in the classic English literature entitled "Charlotte's Web" and its Indonesian translation "Laba-Laba and Jaring Kesayangannya", which were scrutinized using content-based mixed methods. The emotional meanings were explored using Jovanović’s (2004) theory. The conversion was identified by cultivating Cuenca (2006)'s and Baker (1992)’s proposals. Meanwhile, the implication of the conversions was observed by considering formal correspondence and meaning equivalence. The results suggest that: first, different types of emotional meaning are found in both ST and TT, i.e. anger, disagreement, enquiry, ensurement, hesitation, irritation, pleasure, realization, relief, soothe, and triumph. Second, four conversion strategies are deployed by the translator from English to Indonesian version, i.e. (1) conversion using a similar form and meaning; (2) conversion using a similar form, meaning, and literal translation (triplets) and (3) the conversion through deletion, with the first one as the most often used. Third, while the first two conversions were applicable for producing equivalent expressions, whereas the translator, on the whole, maintains a formal correspondence that equalizes the meaning, the last results in some degree of emotional meaning deviations. This study has demonstrated how inappropriate strategies of rendering interjections may cause distortion of the author’s original idea and ruin or reduce the emotional expressiveness in the text. Keywords: conversion, cognitive interjections, literary translation, translation equivalence